Prevalence and determinants of exposure to family planning messages among reproductive age women in five Sub-Saharan African countries: a multilevel analysis of 2021–2023 demographic and health surveys - Kidist Endalkachew Admasu; Tadesse Tarik Tamir; Mekdes Tigabu Alemu; Gebreeyesus Abera Zeleke; Alebachew Ferede Zegeye (BMC Women's Health)
Abstract Introduction Women in many developing nations lack information about family spacing and contraceptives. Thus, nations worldwide frequently employ mass media to promote family planning and raise public awareness. Therefore, this study aims to ascertain the prevalence and factors associated with exposure messages on family planning among reproductive-age women in five sub-Saharan African countries. Method Demographic and Health Survey data (2021–2023) from five sub-Saharan African countries (n = 48,133 women of reproductive age) were analyzed using STATA 17. Multilevel mixed-effects logistic regression identified significant factors (p < 0.05) associated with family planning message exposure, interpreted via adjusted odds. Result The prevalence of exposure to family planning messages was 56.29%. Maternal age groups 25–34 and 35–49 had adjusted odds ratios (AOR) of 1.49 and 1.59, one by one (95% CI: 1.36–1.64, 1.44–1.76). Maternal education levels primary, secondary, and higher had AORs of 1.52, 2.08, and 3.17, accordingly with (95% CI: 1.43–1.61, 1.95–2.23, 2.75–3.66) sequentially. Employed women had an AOR of 1.61 (95% CI: 1.54–1.69). Middle and rich socioeconomic statuses had AORs of 1.49 and 2.16, respectively with (95% CI: 1.41–1.58, 2.03–2.30). Distance to a health facility being a significant problem had an AOR of 1.09 with (95% CI: 1.04–1.14). Antenatal care (ANC) visits of 1–3 and ≥ 4 had AORs of 1.43 and 1.58, in turn with (95% CI: 1.25–1.46, 1.39–1.78). Community variables included urban residence (AOR: 1.16, 95% CI: 1.09–1.23), low illiteracy (AOR: 0.70, with 95% CI: 0.64–0.77), and low poverty (AOR: 1.19, 95% CI: 1.09–1.23). Country categories Burkina Faso, Ghana, Mozambique, and Tanzania had AORs of 1.00, 1.62, 0.55, and 0.73, respectively. These factors were significantly associated with exposure to family planning messages. Conclusions This study concluded that exposure message on family planning among reproductive-age women in five sub-Saharan African countries were high. Both individual and community-level variables as determinants of exposure message on family planning.